Effect of Levels and Time of Nitrogen Application on Yield and Economics of Rice - Ajmal, K. K.; Goverdhan, M.; Sridevi, S.; Suresh, K. (International Journal of Economic Plants, 2022)
A field experiment was conducted on yield and economics of rice during 2017 at Agriculture Research Institute, Rajensranagar. The study was conducted with 10 treatments and laid out in randomized block design with 3 replications. The soil of the experimental site was clay loam in texture, slightly alkaline in reaction, non-saline, low in organic carbon and available nitrogen, high in available phosphorous and potassium.Among the different time and dose of application of nitrogen, the highest panicle m-2 (309.3), panicle length (23.9 cm), number of filled grains panicle-1 (103.2),number of total grains panicle-1 (118.1), test weight (23.9 g), grain yield (4514 kg ha-1), straw yield (5470 kg ha-1) and B: C ratio (1.99)were recorded highest with application of 160 kg N ha-1 25% each at sowing, 20 DAS, 40 DAS and 60 DAS compared to the other treatments. However, growth recorded with 160 kg in 4 equal splits was found to be on par with the growth in the treatments having 160 and 140 kg N ha-1applied at various splits and with application of 120 kg N ha-1 in 4 equal splits at sowing, 20 DAS, 40 DAS and 60 DAS. The lowest observation wasfoundin the farmer’s practice with the application of nitrogen at 120 kg ha-1 N in 3 splits with 12% at sowing, 44% at 40 DAS and 44% at 60 DAS.